Effect of Sihogyeji-tang on functional dyspepsia: a systematic review and meta-analysis - Bae, Hanbum; Kim, Jinsung; Kim, Soyeon (Frontiers in Pharmacology, 2025)
IntroductionFunctional dyspepsia (FD) has a global prevalence of approximately 15% and is characterized by chronic symptoms with an unclear etiology. Herbal medicines, owing to their multifaceted mechanisms, are promising therapeutic options for FD. This study aimed to establish medical evidence for the use of Sihogyeji-tang (SG), a herbal medicine, in the treatment of FD, thereby providing clinically relevant evidence for both patients and healthcare practitioners.MethodsA comprehensive search was conducted on 24 June 2025, in the following databases—four English databases (CINAHL, EMBASE, Cochrane Database, and PubMed), five Korean databases (RISS, KISS, NDSL, DBPIA, and OASIS), one Japanese database (J-Stage), and three Chinese databases (CNKI, Wanfang, and VIP)—to identify eligible studies for this review. Randomized controlled trials investigating the use of SG for the treatment of FD were included. The risk of bias was assessed using the Cochrane Risk of Bias tool and the results were synthesized with Review Manager 5.4.ResultsData from 12 randomized controlled trials involving 805 individuals were included in the meta-analysis. SG demonstrated a significantly higher total effective rate than prokinetic agents (risk ratio [RR]: 1.28, 95% confidence interval [CI]: 1.19–1.37, P < 0.00001). SG also resulted in a significantly greater reduction in symptom severity, as measured by the traditional Chinese medicine (TCM) symptom total score, compared with the control group (standardized mean difference: −1.10, 95% CI: −1.53 to −0.68). The incidence of adverse events was significantly lower in the SG group than in the control group (RR: 0.26, 95% CI: 0.09–0.76, P < 0.05). The quality of evidence was rated as moderate for the total effective rate, very low for the TCM symptom score, and low for adverse events.DiscussionThe findings suggest that SG may be more effective and safer than prokinetic agents for FD. However, the certainty of the evidence is limited by methodological weaknesses in the included studies. To validate these results and support the clinical adoption of SG in FD, robust and extensive randomized controlled trials are needed.Systematic review registration[https://www.crd.york.ac.uk/PROSPERO/], identifier [CRD420251041781].